A Design of Lowpass Filter with High Suppression in Stopband. Issue 2 (March 2021) - Jin, Liang; Li, Xiaojun
Abstract: Beeline compact microstrip resonance cell (BCMRC) is improved to reduce return loss. A lowpass filter in terahertz band is formed by two improved BCMRC cells and a central microstrip, which make the two cells incorporate into one structure successfully. The filter has widened stopband and high suppression characteristic under the same filter's order. The optimized result is proposed with an insertion loss of less than 0.4dB in the lowpass band from 0 to 100GHz. The stopband with attenuation more than -20dB is from 140GHz to 350GHz, and the stopband with attenuation more than 40dB is from 158GHz to 312GHz. The size of the low-pass filter is 0.8mm×0.4mm, and this filter can be used in mixer or other devices of terahertz.